Single-resistance-controlled current-mode quadrature sinusoidal oscillator using single CCCFTA with grounded elements - Srisakultiew, Somchai; Siripruchyanun, Montree; Jaikla, Winai (My University, 2013)
This paper presents the current-mode quadrature sinusoidal oscillator employing current controlled current follower transconductance amplifier (CCCFTA). The proposed oscillator can provide two sinusoidal waveforms with high output impedance which makes the proposed oscillator can directly drive load or cascade in current mode circuit without any current buffers. The condition of oscillation (CO) and frequency of oscillation (FO) can be orthogonally controlled by mean of electronic tuning. The circuit consists of only single CCCFTA and three grounded passive elements which is ideal for implementation on an integrated circuit (IC) chip. The predicted results confirmed with Pspice simulation using a BJT technology are agreed with theoretical analysis. The total power consumption is approximately 1.28mW at ±2.5V power supply voltages. © 2013 IEEE.
Keywords: CCCFTA; Current-mode; Integrated circuit; Quadrature oscillator